Photothermal Switching Based on Silicon Mach–Zehnder Interferometer Integrated With Light Absorber - Hanmo Gong; Xi Chen; Yurui Qu; Qiang Li; Min Yan; Min Qiu (IEEE Photonics Journal)
We present an all-optical switch based on photothermal effects in a silicon Mach–Zehnder interferometer (MZI) integrated with a light absorber. The metal–insulator–metal light absorber located near the longer arm of the asymmetric MZI efficiently converts infrared light to heat. Pumped by a continuous-wave 1064-nm laser, the spectral transmittance of the fully etched strip waveguide (half-etched rib waveguide) MZI can be tuned with an efficiency of 38 pm/mW (98.5 pm/mW). Dynamic switching experiments show that the rise/fall time constant of the output probe light is 11.45/10.98 $μ\text{s}$ (8.25/7.13 $μ\text{s}$ ) for the fully etched (half-etched) MZI.